Polarization, Transactionalism and Small States in the International System: Navigating a Fractured Order - Azizian, Rouben (YSU Journal of International Affairs, 2025)
It is widely recognized that the global order is undergoing significant strategic transformations. While these shifts are frequently attributed to heightened geopolitical competition, relatively less scholarly attention has been directed towards the internal dynamics within states, particularly the role of political polarization, in amplifying international tensions. Increasingly polarized domestic politics, coupled with nationalist orientations toward foreign policy, compromise bipartisan consensus and foster transactional, self-interested behavior in international relations. This paper examines the relationship between domestic political polarization and transactional approaches to foreign policy, focusing especially, though not exclusively, on the administration of US President Donald Trump. It explores how these tendencies undermine established international security norms, institutions, and mechanisms. Additionally, the article assesses current and anticipated responses from small states as they adapt to the profound transformations reshaping the international system.